Narzędzia regulacji działalności przedsiębiorstw — kryteria oceny - Pysz, Piotr (Wydział Prawa i Administracji UAM, 1978)
Problems of criteria of initial appraisal of regulation instruments used in economic activities of enterprises in the phase of criteria formulation by central organs were taken up in the article. The importance of these criteria is very great. They influence proposals — formulated in the economic theory — of improving regulation instruments, as well as their definite transformations introduced into the practice of management of economic activity of enterprises. In the first part of the article the necessity of deriving appraisal criteria of regulation instruments from the goal of social production in socialism, has been pointed out. On the base of that assumption an appraisal criterion on a macro-economic scale has been formulated, i.e. maximization of social utility effect of production from a given production potential of the economy. It has been a starting point for formulation— in subsequent considerations — appraisal criteria of regulation instruments in a socialist enterprise. They were placed in spheres of real and regulation economic processes. In the first of these spheres, an appraisal criterion of regulation instruments consists in maximization of social utility effect of production obtained from a part of economy's production potential, being at the disposal of an enterprise. In the regulation sphere, a proper share of an enterprise in economy's regulation processes can be recognized as the criterion.
The Instruments of Regulation of Enterprises Activities